About Database (Db) - Kholmirzayev Ilkhomjon; Khasanov Khojiakbar (Research Parks Publishers, 2021)
This article discusses the stage of development of the database, its types and future plans. A database is a collection of information that is organized so that it can be easily accessed, managed and updated. Computer databases typically contain aggregations of data records or files, containing information about sales transactions or interactions with specific customers. In a relational database, digital information about a specific customer is organized into rows, columns and tables which are indexed to make it easier to find relevant information through SQL or NoSQL queries